Super Absorbent Polymers (SAPs) as concentration preservers in brine deicers for enhanced ice melting capacity - Gage Merke; Maedeh Hesami; Ravi Kiran (Journal of Infrastructure Preservation and Resilience)
Abstract Rock salt brine deicers are among the most prevalent solutions for ensuring safe vehicle operation in snow-prone regions. The efficiency of this solution, however, decreases at extremely low temperatures as it is diluted by melted ice. The objectives of the current study are: 1) to enhance the ice melting capacity of salt brine at extremely low temperatures (0 °C, − 10 °C, − 20 °C, and − 30 °C) using super absorbent polymers (SAPs), and 2) to measure the reduction in the skid resistance of pavements when the SAP-brine solutions are applied on the surface. Five commercially available SAPs are explored for their potential to maintain concentration during the ice melting process. Three weight fractions of SAPs are introduced into traditional sodium chloride (NaCl) brine: 5% by weight replacement of NaCl along with 5% and 10% addition of SAPs in salt brine solution. The experimental work includes quantifying swell rates and capacities of each SAP in saline solution employing a tea-bag method, measuring the ice melting capacity of brines with SAP additives using an in-house ice melting test setup, and assessing reduction in skid resistance employing British Pendulum tester. The results showed that the addition of 5% large particle-sized SAPs enhanced the ice melting capacity by up to 80% compared to the brine solution at − 30°C. Such improvement in ice melting capacity occurred by preserving the salt concentration in the SAP absorbed water. Moreover, the results of the skid resistance test revealed a negligible reduction in skid resistance (up to 2% compared with dry pavement) when 5% large-sized SAP-brine solutions are applied on both Portland Cement Concrete and asphalt pavements.